2003
DOI: 10.1182/blood-2002-06-1881
|View full text |Cite
|
Sign up to set email alerts
|

LSSIG is a novel murine leukocyte-specific GPCR that is induced by the activation of STAT3

Abstract: G-protein-coupled receptors (GPCRs) transduce the signal of a wide variety of chemokines, cytokines, neurotransmitters, hormones, odorants, and others to regulate the biologic homeostasis, including hematopoiesis and immunity. Here we report the molecular cloning of leukocytespecific STAT-induced GPCR (LSSIG), which is a novel murine orphan GPCR with the highest homology to human GPR43. The mRNA expression of LSSIG was clearly induced in M1 leukemia cells during the leukemia inhibitory factor (LIF)-induced dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 17 publications
4
61
0
2
Order By: Relevance
“…GPR43 is also reported to be induced during the differentiation of leukocyte progenitor cells to monocytes or neutrophils and is found mainly in hematopoietic tissues, suggesting that GPR43 could have an important function in the differentiation and/or activation of leukocytes. 18) Karaki et al reported that GPR43 is expressed in peptide YY (PYY)-containing enteroendocrine cells and 5HT-containing mucosal mast cells, 19) which is consistent with physiologic data showing that shortchain FFAs stimulate the release of PYY 20) and serotonin 21) from the ileum and colon. Recently, Ge et al 14) have reported that adipocytes treated with acetate and propionate exhibit a reduction in lipolytic activity.…”
supporting
confidence: 65%
“…GPR43 is also reported to be induced during the differentiation of leukocyte progenitor cells to monocytes or neutrophils and is found mainly in hematopoietic tissues, suggesting that GPR43 could have an important function in the differentiation and/or activation of leukocytes. 18) Karaki et al reported that GPR43 is expressed in peptide YY (PYY)-containing enteroendocrine cells and 5HT-containing mucosal mast cells, 19) which is consistent with physiologic data showing that shortchain FFAs stimulate the release of PYY 20) and serotonin 21) from the ileum and colon. Recently, Ge et al 14) have reported that adipocytes treated with acetate and propionate exhibit a reduction in lipolytic activity.…”
supporting
confidence: 65%
“…As no data on signaling pathways mediating C5aR expression are available, we asked whether the signal transducer and activator of transcription Stat3 might be one likely candidate. This transcription factor was recently shown to regulate expression of another G-protein-coupled receptor (Senga et al, 2003 Fig. 4B, Stat3 translocated efficiently into the nuclei of MCs stimulated with uPA.…”
Section: Upa Upregulates Expression Of C5ar In Mcsmentioning
confidence: 99%
“…Interestingly, the murine ortholog of GPR43 was initially identified as leukocyte-specific STAT-induced GPCR (LSSIG). It was reported that expression of both murine LSSIG and human GPR43 is induced during the differentiation of leukocyte progenitor cells to monocytes or neutrophils, suggesting their involvement in leukocyte function and host defense [11] . SCFAs have long been known to modulate the immune response.…”
Section: Introductionmentioning
confidence: 99%